Continuous teacher education process in school - Abdul Majid, Halimah; Ean, Chuah Beng; Leng, Eow Yee (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2016)
The school administrators in Sekolah Menengah Kebangsaan Putrajaya Presint 11(1) (SMKPP) took the initiatives of doing differently from what they had been doing. Sample of this study consisted of 89 secondary school teachers from SMKPP. Malaysian Education Standards Quality (Standard 4) instrument was used to evaluate teachers’ performance during teaching and learning (T&L) process in the classroom. Paired-samples t-test analyses on teachers’ performance were carried out at .05 level of confidence, between years. Although teachers’ performance was in the range of excellence with the mean score beyond 90 in year 2015, yet there were significant decline within the dimensions of delivery methods, enhancement of mastery learning among students, communication skills, resource application, assessment conducted, questioning skills and overall performance. With the initiatives taken by the school’s administrators through continuous teachers’ education process and renewal practices in school, by mid-year of 2016, teachers started showing improvements with significant results in their communication skills, initiative in applying various resources during T&L processes in the classroom, assessment conducted, questioning skills, classroom management skills and overall performance.